Impact of Mandating The Research Article Based Evaluation as an Assessment for the Pre-Final Year Students for Effective Execution of Final Year Project - Chithiraikannu, Ramarajan; N., Dhivya (Journal of Engineering Education Transformations, 2021)
A Literature survey plays a vital role in preparing the students to carry out research-oriented projects in the final year. The influence of equipping the students with a quality reading of research articles before entering their project semester has not received much attention so far. The present study explores this aspect by introducing students to analyze published research articles as a part of internal assessment in the pre-final year. One batch of Students from B.Tech (Food Technology) was given prior practice for literature reading by mandating it as one of the internal assessment for the subject- Oils and Fats Processing technology, while the other class of students went through the conventional assessment system. The influence of adopting the research article based evaluation in the project outcome attainment was compared for both batches of students in the final year. Facilitating the prior literature reading practice helped students to formulate the project objectives more clearly, critically analyze the reported works of previous researchers, identify realistically the expected challenges in the progress of research, avoid repetition of already explored solutions and finally come up with meaning research outcomes within the stipulated time. The study indicates the need for adopting the research article based evaluation as one of the compulsory assessment for students to help gradually develop research aptitude, rather than expecting such skills to form quickly when they enter final year to take up the project.